Is corporate governance relevant to the quality of corporate social responsibility disclosure in large European companies?. Issue 2 (7th May 2019) - Adel, Christine; Hussain, Mostaq M.; Mohamed, Ehab K.A.; Basuony, Mohamed A.K.
Abstract : Purpose: This paper aims to report on the quality of corporate social responsibility (CSR) disclosure in S&P Europe 350 companies. The paper also examines the impact of corporate governance structure and other firm-specific characteristics on the quality of CSR disclosure in European companies. Design/methodology/approach: The paper uses a disclosure index adopted from Jizi et al. (2014). Moreover, the paper contributes to the CSR disclosure literature by developing a new index that includes all the aspects introduced by the Global Reporting Initiative version 4.The data of CSR reporting are manually collected from the firms' reports. The population and sample of this study are related to 350 companies operating in 16 European countries. Tobit regression analysis is used to test the hypotheses. Findings: The results reveal that directors' ownership, the presence of a CSR committee and firm size positively affect the quality of CSR reporting. Further testing of the independent variables on each CSR sub-category is made. The CSR sub-categories used are, namely, community involvement, employees, environment, social product and service quality, supply chain sustainability and business ethics. The presence of a sustainability committee inside the company is the only factor that shows a strong positive effect on the disclosure of every CSR sub-category and the CSR inclusive index. Research limitations/implications: The limitations of this research are that it focuses exclusively on the effect of the internal corporate mechanisms on the quality of CSR reporting; disregarding the economic, institutional, political and cultural factors that can play a role in influencing sustainability reporting of the companies. Practical implications: Better CSR disclosure leads to the firm having a better image in the society; this, in turn, has implications on firm performance, attracting funds, as well as recruiting and retaining high profile employees. Stakeholders are placing cumulative significance to corporate transparency particularly in the area of CSR. Managers should exert more efforts into not only improving the disclosure of the various facts of CSR but also into using the various media available for disclosure. Companies should take the initiative of establishing a CSR committee to ensure effective formation and implementation of CSR policies and disclosure of CSR activities. Social implications: The CRS research itself bears the merit of social implications. Moreover, the findings of this research pave the way for future researches to examine the effect of the adoption of global CSR initiatives and frameworks on the quality of CSR reporting. Originality/value: This paper contributes to the CSR disclosure literature by developing a new index that includes all the aspects of CSR and exploring the relation between the rarely explored "presence of sustainability committee" and CSR disclosure, as well as testing a vast number of CSR sub-categories that is not extensively covered in previous studies. Moreover, the paper covers a large sample of companies across 16 European countries, in terms of their stand-alone sustainability reports, dedicated chapters of CSR in annual reports, integrated reports, website CSR information and any attachments/links provided on the websites for further CSR documents, brochures or data sheets.